A new compressive scheme to simulate species transfer across fluid interfaces using the Volume-Of-Fluid method. (23rd November 2018) - Maes, Julien; Soulaine, Cyprien
Highlights: Compressive continuous species transfer used to model transport in two-phase system. Superior to standard method for modelling and upscaling interface transfer. Predict accurately interface transfer in deposited thin film. Used to study impact of recirculation in a 2D cavity. Used to upscale interface transfer in complex 2D porous medium. Abstract: We present a new compressive scheme to simulate species transfer across fluid interfaces using the Volume-Of-Fluid method. We show that at high Péclet numbers, the standard Continuous Species Transfer (CST) generates large numerical diffusion in the phase concentration that can lead to inaccurate simulation of interface exchanges in a two-phase system. To solve this issue, the derivation of the concentration advection flux is revisited. We obtain an additional compressive term in the species concentration equation. This novel approach is labelled Compressive CST approach (C-CST). The method and the input of the compressive term are validated by comparison with analytical solutions of two-phase flow and species transport in a 1D tube. The C-CST approach reduces significantly the numerical errors. Then, the approach is used to investigate and upscale species transfer during drainage in 2D porous media.